2015
DOI: 10.1155/2015/920431
|View full text |Cite
|
Sign up to set email alerts
|

Bavachalcone Enhances RORαExpression, Controls Bmal1 Circadian Transcription, and Depresses Cellular Senescence in Human Endothelial Cells

Abstract: The circadian clock regulates many aspects of (patho)physiology in the central nervous system and in the peripheral tissues. RAR-related orphan receptor α (RORα), an orphan nuclear receptor, is involved in circadian rhythm regulation, including regulation of cardiovascular function. Bavachalcone, a prenylchalcone, is a major bioactive chalcone isolated from Psoralea corylifolia. This natural ingredient activated RORα1 luciferase reporter activity on drug screening. In addition, bavachalcone induced RORα1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Several studies have reported that EPO activates EPC differentiation [ 5 , 6 ] and AMPK activity [ 17 , 20 ]. However, in previous studies [ 34 ] and the present study (Figure 7B ), we demonstrated that BavaC activates RORα1. DNA sequence analysis revealed that the binding site of RORα is present in human and rat EPO promoters (Figure 7A ).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Several studies have reported that EPO activates EPC differentiation [ 5 , 6 ] and AMPK activity [ 17 , 20 ]. However, in previous studies [ 34 ] and the present study (Figure 7B ), we demonstrated that BavaC activates RORα1. DNA sequence analysis revealed that the binding site of RORα is present in human and rat EPO promoters (Figure 7A ).…”
Section: Discussioncontrasting
confidence: 69%
“…Numerous studies have confirmed that RORα regulates circadian rhythm and metabolism [ 30 32 ]. In a previous study, we found that a natural compound bavachalcone (BavaC, CAS No.28448-85-3, derived from a traditional Chinese medical herb Psoralea corylifolia Linn) activates AMP-activated protein kinase activity and MnSOD expression [ 33 ] and induces RORα expression at the luciferase reporter, mRNA, and protein levels, partially inhibiting endothelial cell senescence [ 34 ]. However, the role of RORα in the proliferation and differentiation of EPCs is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrated that bavachalcone not only prevents endothelial cells senescence [56,57], but also promotes differentiation of bone marrow stem cells and endothelial progenitor cell via EPO/AMPK pathway (our unpublished data). Effects of kidney-nourishing herbs on differentiation of bone marrow mesenchymal stem cells also have been reported recently.…”
Section: Reinforcing Kidney Drugs and Diseasessupporting
confidence: 62%
“…Dietary lipoic acid supplementation could up-regulate circadian genes in the positive arm ( Bmal1 and Npas2 , a functional homologue of the Clock gene) and down-regulate genes in the negative arm ( Per2, Per3, Nr1d2 ) of the circadian core oscillators ( Finlay et al, 2012 ). Bavachalcone, a natural medicine ingredient, has a pharmacological function in regulating RORα ( Dang et al, 2015 ). Thus, alteration of circadian clock could be a pharmacological basis of therapeutics.…”
Section: Discussionmentioning
confidence: 99%